2017
DOI: 10.1002/hep.29104
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular systolic function is associated with sympathetic nervous activity and markers of inflammation in cirrhosis

Abstract: LV systolic function is enhanced in cirrhosis due to augmented adrenergic tone and modulated by treatment with beta-blockers; acute afterload stress induces a deeper impairment of systolic function in patients with more advanced degrees of vasodilatation and inflammation; these changes in LV function related to cirrhosis can be assessed using robust echocardiographic methods. (Hepatology 2017;65:2019-2030).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
80
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(87 citation statements)
references
References 42 publications
5
80
1
1
Order By: Relevance
“…This could also be substantiated by the data provided by other groups . An enhancement of sympathetic nervous activity resulting in an augmented systolic function might also play a role in the pathophysiology of the increase of myocardial contractility as recently shown . Especially in Child‐Pugh C patients, STE parameters were independent predictors of transplant‐free survival and time to transplantation.…”
Section: Discussionsupporting
confidence: 61%
“…This could also be substantiated by the data provided by other groups . An enhancement of sympathetic nervous activity resulting in an augmented systolic function might also play a role in the pathophysiology of the increase of myocardial contractility as recently shown . Especially in Child‐Pugh C patients, STE parameters were independent predictors of transplant‐free survival and time to transplantation.…”
Section: Discussionsupporting
confidence: 61%
“…However, using the tools noted above, it has been recently demonstrated that systolic function is not depressed but actually enhanced in patients with cirrhosis and directly correlates with the severity of the liver disease (Child‐Pugh and Model for End‐Stage Liver Disease scores) . This has been attributed to a direct inotropic effect induced by the activation of the sympathetic nervous system (SNS) in cirrhosis . The enhanced GLS in patients with end‐stage liver disease described by Jansen et al further corroborates this finding, although the potential confusion caused by the afterload‐dependence of myocardial strain should also be taken into account.…”
mentioning
confidence: 75%
“…Albeit to a lesser extent than ejection fraction (EF), previous experimental and clinical validation studies have shown that the index used global longitudinal strain (GLS), is also dependent on afterload, and may have limited sensitivity to account for myocardial contractility. Recently, we have demonstrated that other echocardiographic indices based on the analysis of intraventricular flow (ie, intraventricular pressure gradients) can help resolve these limitations, particularly in advanced cirrhosis …”
mentioning
confidence: 99%
See 2 more Smart Citations